The results of the treatment of right ventricle myocardial infarction - Rafajlovski Saša I.; Orozović Vjekoslav; Rađen Goran; Ristić-Anđelkov Anđelka (Vojnosanitetski Pregled)
Aim. To present the results and experience in diagnosing and treating of patients with acute right ventricle infarction, during the period of hospitalization of one month, with adjuvant analyses of the obtained results in the period of fifteen years. Methods. Acute right ventricle infarction porved clinicaly, enzymologicaly, by ECG, echochardiographically or scintigraphically we treated with thrombolitic therapy within first six hours after admittion, with salvaged PTA in case of the cardiogenic shock or AV block IIº−IIIº despite of thrommbolitic therapy, or with postponed PTA within first month of intrahospital treatment. Results. In the period from 1990 to 2004, 3 225 patients of both sexes were treated for acute myocardial infarction at the different localization in patients' at the mean age of 53.7 ± 5.8. One-hundredthirty - nine (43.9%) patients were treated with thrombolitic therapy according to the speed up protocole. Heparin was administered to 160 (50.7%) patients with water load, and 17 (5.4%) patients had the primary percutaneous transluminal coronary angioplasty (PPTCA), so that the mechanical blood flow could be established, by the implantation of a stent when necessary. In 316 patients with right ventricle infarction, 58 (18.3%) had postponed and salvaged percutaneous transluminal coronary angioplasty (PTCA). Twenty-two (15.8%) patients had thrombolitic therapy, whereas 36 (22.5%) patients were treated with heparin. We had a successful balloon dilatation in 21 (36.2%), whereas 32 (55.2%) patients had 1−3 intracoronary stents inplanted, depending upon the necessity, and 5 (8.6%) patients from this group were sent to surgical intervention. In the group of 214 (67.7%) patients treated with heparin or thrombolitic therapy combined therapy, with PTCA, 12 (5.7%) patients died, whereas in the group of 124 (39.3%) patients treated only with heparin 26 (16.2%) patients died, statistically significant difference (p < 0.001, χ2 = 18.423). Was noticed n the group of 1 204 patients with inferoposterior infarction, 122 (10.1% ) patients died. In the group of 316 patients with right ventricle infarction, 38 (12%) died. In the group of 888 control patients with inferoposterior infarction, but without right ventricle infarction, 84 (9.4%) patients died. In the group of 2 021 patients (62.2%) with anterior infarction, 248 (12.3%) died. Conclusion. The obtained results showed that the patients with right ventricle infarction, due to the great expansion of necrosis and the involvement of the inferoposterior wall of the left ventricle, as well as the ischemia of sinus and AV nodes, were the patients of a high risk. That was why it was essential to do urgent widening of the artery to reestablish blood flow either by using drugs or by means of mechanical methods.